F - Kehlmann, Daniel, 1975- (Pantheon Books, 2014)
Having a profound experience on a hypnotist's stage in spite of not believing in magic, Arthur abruptly abandons his family in the middle of the night and becomes a famous author while his sons grow into men shaped by loss and doubt.